Do Socialist Countries Suffer a Common Business Cycle? - Ickes, Barry W. (The Review of Economics and Statistics, 1990)
The nature and characteristics of economic fluctuations in Eastern European Centrally Planned Economies are analyzed. When cycles are identified by the deviation from a fitted deterministic trend, they are seen to coincide temporally. This common variation is found for Net Material Product (NMP) and Investment. The implications of the common variation of CPE cycles are discussed. Possible explanations of this phenomenon are discussed with emphasis on a possible link via trade. We then examine the possibility that the time series contain unit roots. We are unable to reject this hypothesis for the variables in question. This suggests using procedures for detrending nonstationary time series suggested by Beveridge and Nelson. Such an analysis is performed and the implications are discussed. We find that there remains some common variation in the cyclical component of output, but to a lesser extent. The implications of these findings for future research on CPE cycles are discussed.